2016
DOI: 10.2460/javma.248.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the labor market for veterinary technician specialists in 2013

Abstract: Results suggested that gender, work experience, and job characteristics were significantly associated with pay rate for VTSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This aligns with research in Australia and overseas linking femaledominated fields with a wage 'gap' amounting to lower starting salaries and future earning potential of graduates(Lindsay 2014). Likewise, a study of the labour market for USA credentialled VT specialists revealed males having a higher likelihood of greater pay(Norkus, Liss & Leighton 2016): a trend reflected in salaries of the albeit, small number of males in this study. To improve salaries overall, Australian veterinarians could delegate more effectively to utilise the enhanced skill set of these support personnel.…”
supporting
confidence: 51%
“…This aligns with research in Australia and overseas linking femaledominated fields with a wage 'gap' amounting to lower starting salaries and future earning potential of graduates(Lindsay 2014). Likewise, a study of the labour market for USA credentialled VT specialists revealed males having a higher likelihood of greater pay(Norkus, Liss & Leighton 2016): a trend reflected in salaries of the albeit, small number of males in this study. To improve salaries overall, Australian veterinarians could delegate more effectively to utilise the enhanced skill set of these support personnel.…”
supporting
confidence: 51%